On intellectual capital efficiency and shariah governance in Islamic banking business model - Nawaz, Tasawar; Roszaini, Haniffa; Mohammad, Hudaib (John Wiley & Sons Ltd., 2021)
This paper empirically investigates whether intellectual capital (IC) and shariah governance jointly affect the economic performance of Islamic banks (IBs). In contrast to prior research, this paper disaggregate IC and corporate governance features and examine whether the two are jointly related to economic performance. These relationships are further explored before, during and after the financial crisis based on a sample of 64 Islamic banks operating in different regions during the period 2007–2014. The required data to calculate different constituents of IC efficiency and governance mechanism is hand collected from 512 annual reports. After controlling for other corporate governance and bank‐specific characteristics (operational type, bank size, listing status, risk, type of auditor, accounting standard and region), we find both intellectual capital efficiency and shariah governance proxies (size and dominance of prominent scholars of shariah supervisory board) to have a significant positive relationship with accounting measure of performance. However, based on market performance measure, only one proxy for shariah governance mechanism, that is, prominent scholars on SSB, is found to be significant but in the negative direction. These results provide important insights into the relationship between IC efficiency, corporate governance and performance in Islamic banking business model and have policy and practical implications.